Evaluation of three measures of cardiorespiratory fitness in independently ambulant stroke survivors. (3rd July 2019) - Dunn, Ashlee; Marsden, Dianne L.; Barker, Daniel; van Vliet, Paulette; Spratt, Neil J.; Callister, Robin
ABSTRACT: Measuring cardiorespiratory fitness (CRF) in the stroke population is challenging. Currently, the recommended method is a graded exercise test (GXT) on an ergometer such as a treadmill or cycle, which may not always be possible. We investigated whether walking tests such as the six-minute walk test (6MWT) and the shuttle walk test (SWT) may be appropriate indicators of CRF in the stroke population. Twenty-three independently ambulant stroke survivors (11 men, age 61.5 ± 18.4 years) within one-year post stroke performed the 6MWT, SWT, and cycle GXT, during which peak oxygen consumption (VO2peak ) and heart rate (HRpeak ) were recorded. There were no differences ( p  > 0.05) in mean VO2peak among the three tests (min-max: 17.08–18.09 mL kg −1  min −1 ). For individuals, small discrepancies in VO2peak between the 6MWT and other tests were greater with higher fitness levels. HRpeak was significantly ( p  = 0.005) lower during the 6MWT. Correlations between VO2peak and performance measures within each test were high (6MWT VO2peak and distance: r  = 0.78, SWT VO2peak and shuttles: r  = 0.73, cycle GXT VO2peak and workload: r  = 0.77) suggesting the performance measures may be clinically useful as proxy measures of CRF. Common comorbidities, such as lower-limb joint pain and poor balance, and participant's fastest walking speed, should inform the choice of CRF test.